Implementation Of DSN-MUI Fatwa No.108/DSN-MUI/X/2016 Concerning Guidelines For Organizing Tourism Based On Sharia Principles In The Hotel Business In East Lombok - Atala Septiana Auliya (Journal of Islamic Business Law, 2022)
Hotels in East Lombok have carried the sharia concept in their operations, but the number of sharia hotels is still very small, this is because there is still a stigma of sharia branding that can cause the hotel business to be quiet and there is a low understanding of the sharia concept. This study aims to explain the management of Sharia hotels in East Lombok and to analyze the application of sharia branding in the perspective Fatwa DSN MUI No. 108/DSN-MUI/X/2016 regarding Guidelines for Tourism Implementation Based on Sharia Principles. This study uses an empirical legal research type with interviews and documentation analyzed qualitatively with a sociological juridical approach. The results of the study are Syariah Lombok Hotel and the Green Hayaq Syariah Hotel have carried the concept of sharia in hotel management but do not yet have a Sharia Supervisory Board that specifically oversees the hotel's operations and regarding the application of the Fatwa DSN-MUI has not yet fully implemented.